2000
DOI: 10.3171/foc.2000.8.3.4
|View full text |Cite
|
Sign up to set email alerts
|

The “presyrinx” state: is there a reversible myelopathic condition that may precede syringomyelia?

Abstract: Object Alteration of cerebrospinal fluid (CSF) flow has been proposed as an important mechanism leading to the development of syringomyelia. We hypothesize that a “presyrinx” condition due to potentially reversible alteration in normal CSF flow exists and that its appearance may be due to variations in the competence of the central canal of the spinal cord. Methods Five patients with clinical evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 40 publications
3
104
0
2
Order By: Relevance
“…These findings were consistent with presyrinx. 5) The serial neuroimaging changes suggested that infratentorial hygroma was the cause of the subsequent other complications such as hydrocephalus and presyrinx. Although the arachnoid membrane seemed to be preserved during operation, an invisible tear present in the area of FMD may have acted as a one-way valve in the postoperative period.…”
Section: Case Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings were consistent with presyrinx. 5) The serial neuroimaging changes suggested that infratentorial hygroma was the cause of the subsequent other complications such as hydrocephalus and presyrinx. Although the arachnoid membrane seemed to be preserved during operation, an invisible tear present in the area of FMD may have acted as a one-way valve in the postoperative period.…”
Section: Case Reportmentioning
confidence: 99%
“…5) To prevent the progression of presyrinx to syringomyelia, which might cause intractable pain or persistent neurological deficits, immediate normalization of CSF circulation around the foramen magnum was warranted. 5,8) We preferred re-exploration, which offered more straightforward treatment for the re-establishment of CSF circulation. The hygroma was thought to be the result of the check-valve phenomenon, but the point of leakage was difficult to detect.…”
Section: F Suzuki Et Almentioning
confidence: 99%
See 3 more Smart Citations